Error Analysis in Writing Narrative Text of Seventh Graders of Secondary School - Galang Sumarna Putra; Mundriyah; Suhud Aryana (IKIP Siliwangi, 2026)
This study aims to identify and examine errors commonly committed by seventh grade students. It was conducted to support teachers improve the students’ writing proficiency in English by identifying students’ weaknesses and mistakes in using the language in the written medium. A class of 30 students was selected to participate in this research which they were asked to write an essay about narrative text. The essays were subjected to error analysis by using a criterion for grade 7 English standards which was adapted from Chanquoy’s error classification. The results were then analysed and validated. They significantly showed that students had weaknesses in the use of punctuation, grammar (specifically verb tenses), and capitalization. Other mistakes included spelling, subject-verb agreement, preposition, conjunction, and pronouns. The results are expected to help English teachers to develop their classroom strategies and emphasize more on the common mistakes made by the students. In this regard, students are expected to improve their writing skills, specifically in those topic areas.